PENGUKURAN NILAI INDUKTANSI PELAT ALUMINIUM BERDASARKAN VARIASI KAPASITANSI MENGGUNAKAN MODUL EVB LDC 1000 - Cinryani Cinryani; Lazuardi Umar; Salomo Salomo; Maksi Ginting (Universitas Riau, 2020)
The method that has been done in metal thickness measurement is a plate thickness measurement method using an eddy current based sensor. Eddy current sensors can measure the thickness of non-magnetic metal layers through an inductance relationship with variations in thickness where the thickness used for Cu is 0.4 mm, 0.9 mm, 1.5 mm, 2 mm, 4 mm, while Al is used ie 0.4 mm, 0.5 mm, 1 mm, 1.2 mm, 1.5 mm, 1.8 mm, 2 mm, 2.2 mm, 4 mm, 5 mm with a single frequency of 1 Hz with a capacitance value of C0 5 pF. The inductance vs. thickness curve for aluminum and copper has an exponential relationship. The distance between the sensor and non-magnetic material is kept constant at 2 mm. Variations in the value of capacitance C0 used in the measurements are then varied to 100 pF, 200 pF, and 300 pF to see the effect of inductance on the thickness of the plate as a function of the capacitor (C) oscillation.